Dealing with Patients with Behavioural Problems After Acquired Brain Injury: Nurses’ Experiences with the Antecedent Behaviour Consequence Method - Climmy Pouwels; Peggy Spauwen; Caroline van Heugten; Resi Botteram; Ieke Winkens; Rudolf Ponds (Journal of Long-Term Care, 2024)
Context: Behavioural problems are common after brain injury and can cause feelings of distress in the nursing staff, which can in turn have a negative influence on the behaviour of the patient. Nurses often do not feel they have the necessary skills to apply behavioural interventions in daily practise. They may benefit from the ABC (Antecedent-Behaviour-Consequence) method.